Factors Related to the Quality of Nursing Care Documentation - Susiana, Endang; Wahyuni, Erna Dwi; Asmoro, Candra Panji (Fundamental and Management Nursing Journal, 2019)
Introduction: Nursing documentation is a legal aspect that protects nurses in providing nursing services, but incomplete documentation is still found. The purpose of this study was to analyze the relationship between motivation, supervision, and workload with the quality documentation of nursing care in the Medical Inpatient Dr. Soetomo Hospital Surabaya.Method: This study used a descriptive correlation design with a cross-sectional approach. The population was 135 nurses and 100 nurses were obtained by simple random sampling. Independent variables are motivation, supervision, and workload. The dependent variable is the quality documentation of nursing care. Data were obtained by motivation, supervision and observation sheets: TMS (Time Motion Study), SAK (Nursing Standards) and analyzed with Spearman's Rho, Regression Logistic with α=95%.Result: There was a relationship between motivation (p = 0,000; r = 0,363) with the quality of nursing care documentation, there was a relationship between supervision (p = 0,012; r = 0,310) and the quality of nursing care documentation and there was a relationship between workload (p = 0,002; r = 0,299) with the quality of nursing care documentation.Conclusion: There was a relationship between motivation, supervision, and workload with the quality of nursing care documentation. It is known that motivation was the most related factor in the quality of nursing documentation.